Evaluation of IT Governance Maturity Level in Stationery Stores Using COBIT 5 - Yahu, Mikhael Neta; Septian, Daniel Marvelino; Ghifari, Nabil Najwa Al; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (INSTALL: Information System and Technology Journal, 2024)
In the operation of a company that utilizes and implements information technology components, a framework is needed to ensure that all information technology components are operational in accordance with the goals that the company wants to achieve. The use of information technology components in the business sector requires companies to have good information technology governance skills so that the identification and implementation of information technology component components work optimally. To measure the level of maturity and ensure that the information technology components used in the ATK store are implemented and run properly and ensure whether the information technology component provides benefits for the ATK store business. The data collection method to measure the maturity level at the ATK xyz take was carried out by direct interviews and questionnaires for the staff responsible for the operation of the information technology component at the ATK xyz take. Based on the results of measuring the maturity level using the COBIT 5 framework, it was found that the maturity value was at a value of 3.25 or at level 3 (established). At this level, the IT governance process is considered good and runs optimally and comprehensively. The gap between the current and expected IT governance processes is at 1.67. This gap indicates that the current IT governance process is quite good. In the future, it is recommended to use more domains from COBIT 5 as the focus of the assessment area, both the Governance area and the Management area, so that the assessment becomes more comprehensive with a more varied research focus.